The Effect of Gender Diversity on Board of Commissioners and Directors to Firm Performance: the Moderating Role of ESG Performance in Indonesian Listed Companies From 2021-2023 - Ghea Laili Putri Garien; Susi Sarumpaet (International Journal of Economics and Management Sciences, 2026)
This study investigates the interconnected roles of board gender diversity and Environmental, Social, and Governance (ESG) performance on firm performance within Indonesia's distinctive two-tier corporate governance system. Utilizing a panel dataset of 80 companies listed on the Indonesia Stock Exchange from 2021 to 2023 and employing a fixed-effects regression model, the analysis measures gender diversity on both the Board of Commissioners (BOC) and Board of Directors (BOD) using the Blau Index, with firm performance proxied by Tobin's Q and ESG performance sourced from Refinitiv Eikon scores. The empirical results reveal that gender diversity on both the BOC and BOD does not have a statistically significant effect on firm performance, failing to support agency, upper echelons, and gender socialization theories. Furthermore, ESG performance demonstrates a significant negative direct effect aligning with the trade-off perspective that current implementation costs outweigh benefits. Crucially, the analysis finds that ESG does not moderate the board diversity-performance relationship, as both interaction terms are statistically insignificant. These findings collectively indicate that the potential governance and strategic advantages of board gender diversity are not being realized in the Indonesian context. The study concludes that this is attributable to several structural barriers, including tokenistic board appointments, the early-stage and often symbolic nature of ESG adoption focused on compliance rather than integration, and a weak institutional environment characterized by voluntary frameworks and socio-cultural constraints that limit the substantive influence of women in governance roles.